Egy térszerkezeti modell - Baráth, Etele (Tér és Társadalom, 1987)
The conceptual model outlined in the paper was elaborated in order to support regional planning. It is a resource oriented model involving both natural and societal resources . The model aims to facilitate the analysis of inter-relationships among the components of spatial development processes. ln its first part the paper reviews some of the issues which urge a system oriented approach in the study of the Hungarian settlement network. It assumes that Hungarian urbanists faíled to give answers to basic theoretical questions therefore are unable to provide a reliable background for settlement planning and settlement development. While social scientists manifest an increasing interest in settlement development, urbanists are largely índifferent to social issues. Their scope of interest is stíll restricted to technical problems: the ’reformist wave’ in Hungary seems to have passed by the urbanists . The conceptual model outlined in the paper derives regional and settlement development processes from societal needs and pools their operating factors into two subsystems, the so-called sectoral und the so-called spatial systems, which are dialectically related to each other. The second part of the paper gives insight into the contents of spatial analyses made with the application of the model.